IMPLEMENTASI STRATEGI PEMBELAJARAN ANTICIPATION GUIDE PADA PEMAHAMAN MEMBACA SISWA - Hemas Haryas Harja Susetya (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
The background of the problem in this study is the effectiveness of the anticipation guide strategy used in the learning process. At this time with the development of education that is increasingly rapid, the curriculum used is a curriculum that is considered capable of maximizing the learning process. The use of the 2013 curriculum is a demand for educators to further maximize the learning process in which students are required to be more active in the classroom. The purpose of this study was to determine the effectiveness of the anticipation guide strategy in students' reading comprehension skills. In this research process, the writer takes data by conducting an experimental class which in one class is divided into two groups. The first group of authors asked students to explain the subject matter without any prior explanation by an author, while the second group of authors explained the scope of the material to be studied and then asked students to re-explain what had been understood from the results of listening and listening to the writer. So with this experiment the author can see the effectiveness of the anticipation guide strategy with the results that have been tested. In this study, the authors see that the anticipation guide strategy is suitable for use in the learning process by means of educators explaining in advance the material to be taught to students so that students can understand the subject matter optimally. Keywords: effectiveness, learning strategy, anticipation guide.